EPA, DHA, and coenzyme Q10 as nanonatruceuticals adjuvants in therapy against Covid-19 - Santiago Herrero (Indonesian Nutrition Association, 2022)
Up today, August 28, 2021, about 215,5 million people have been infected with the coronavirus SARS-CoV-19 and with a global death of 4,5 million. US deaths 636,7K (fatality 0,194) and Spain 97,7K (fatality 0,208). Many protocols have been implemented for the treatment of COVID-19 since the beginning of this pandemic throughout the world, but specific guidelines have never been made by the different international Societies with respect to unifying criteria for action given the diversity of treatments that do not have had adequate clinical evidence. Since the vaccination campaign began, treatment has focused on hospitalized patients, but no prophylactic or early-onset treatment has been offered, limiting their access simply to infections with serious symptoms.